1989
DOI: 10.1203/00006450-198906000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aldosterone and Atrial Natriuretic Peptide on Water and Electrolyte Homeostasis of Sick Neonates

Abstract: ABSTRACT. To clarify fluid homeostasis in neonates, 27 sick neonates (51 had respiratory distress syndrome, 1 2 had hyperbilirubinemia, and nine were low birth wt infants) were studied on 13 to 1 5 days of age. The infants were stabilized and required neither ventilation nor intravenous fluids a t the time of study. All infants were breast fed, and their sodium intake ranged from 1.7 to 2.9 (2.2 f 0.3) mEq/kg/d. Gestational age ranged from 30 to 39 (34 f 3.4) wk and birth wt ranged from 1080 to 3280 (2,070 f 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Plasma ANF levels were determined in 42 infants between the second and seventh day of life by radioimmunoassay, as reported previously (5). Informed consent was obtained from the parent of each infant.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma ANF levels were determined in 42 infants between the second and seventh day of life by radioimmunoassay, as reported previously (5). Informed consent was obtained from the parent of each infant.…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, only plasma levels of atrial natriuretic peptide and aldosterone were correlated with gestational age [9]. It was shown that 15-day-old infants (born at week 30-39 of gestation) have higher levels of atrial natriuretic peptide than adults, and that neonates born at a conceptional age of ^32 weeks have higher aldosterone levels than those aged 34 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…age of filtered Na § in premature infants (Siegel, 1982), even though their plasma levels of aldosterone are high (Kojima, 1989), indicate that renal epithelia are partially unresponsive to aldosterone. Furthermore, the renal response of suckling rats is largely insensitive to aldosterone (Stephenson et al, 1984) and the faecal Na § loss and urinary excretion of Na § are not correlated with plasma aldosterone in new-born calves (Safwate et al, 1982).…”
Section: Introductionmentioning
confidence: 99%